Pengaruh Alkohol sebagai Pemicu Tindak Pidana: Implikasi Terhadap Pencapaian Tujuan Pembangunan Berkelanjutan - Alexandro Aldikan Matio Panjaitan; Fabian Beryl Allen Vidia; Raymond Erlangga Siringoringo; Yuliana Yuli W (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Alcoholic drinks are often the main factor in various crimes, including assault, robbery and murder. Excessive alcohol consumption can cause loss of self-control, which can lead to unlawful acts such as traffic accidents, rape, assault, theft and domestic violence. This behavior disturbs public peace and has the potential to hinder the achievement of several Sustainable Development Goals (SDGs), such as good health (goal 3) and peace and justice (goal 16). This article aims to analyze the influence of excessive alcohol consumption on increasing criminal acts and its relationship to achieving the SDGs. Using qualitative methods with a normative legal approach and literature study, this research examines legal norms, statutory regulations and other relevant legal documents. Data analysis was carried out descriptively to identify the relationship between alcohol consumption, criminal acts, and their impact on achieving the SDGs. The research results show that excessive alcohol consumption contributes significantly to the increase in violent crimes and is a risk factor in cases of domestic violence and sexual harassment. Apart from the negative impact on physical and mental health, drunken behavior also hinders the achievement of SDGs, such as goal 3, goal 5 (gender equality), and goal 16. Although regulations in Indonesia have attempted to regulate the consumption and distribution of alcohol, their effectiveness still requires improvement. It is hoped that with a comprehensive approach and stricter policies, the negative impacts of alcohol consumption can be minimized, supporting the achievement of sustainable development goals.